2011
DOI: 10.1111/j.1754-4505.2011.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugar consumption and preference among Mexican, Chinese, and Nigerian immigrants to Texas

Abstract: This pilot study investigated the relationship between sugar consumption/ preference and the length of residence in the U.S. among certain immigrant groups. The study sample consisted of 213 volunteers from community organizations and church groups, of Nigerian (45%), Mexican (31%), and Chinese (24%) descent. Data were collected on demographics, sugar consumption/preference (24-hour dietary recall), and oral health status. The age of respondents varied from 18 to 93 years with a mean age of 37.0 ± 11.7 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Six studies examined mean daily energy intake, but not all reported standardising intakes to body weight or recommended intakes, thus making them difficult to compare and interpret [ 33 , 39 , 43 , 45 , 46 , 47 ] ( Table 2 ). Many ethnic groups in the US and Oceania consumed well in excess of their protein requirements [ 39 , 41 , 43 , 46 ]; however, the Kamba ethnic group in Kenya had significantly lower mean daily protein intakes than any other group (male: 49.60 g/day, female: 38.50 g/day) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies examined mean daily energy intake, but not all reported standardising intakes to body weight or recommended intakes, thus making them difficult to compare and interpret [ 33 , 39 , 43 , 45 , 46 , 47 ] ( Table 2 ). Many ethnic groups in the US and Oceania consumed well in excess of their protein requirements [ 39 , 41 , 43 , 46 ]; however, the Kamba ethnic group in Kenya had significantly lower mean daily protein intakes than any other group (male: 49.60 g/day, female: 38.50 g/day) [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Asian groups in Oceania also had significantly lower total fat intakes than White, Pacific and Maori groups [ 39 , 41 ]. Carbohydrate intake was lowest among Asian groups compared to other groups in Australia, New Zealand and the US [ 39 , 41 , 45 ]. Minimal differences in carbohydrate intake between American White and Black groups were noted [ 43 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five (5/51, 9.8%) studies reported varying daily carbohydrate consumption and inadequate fibre consumption among Chinese immigrants in Canada and the United States [ 20 , 32 , 34 , 54 , 62 ]. Three studies reported carbohydrates making up over 50% of total energy intake, [ 62 ] with daily intake ranging from 185 to 258 g per day [ 34 , 54 , 62 ]. Three studies reported fibre consumption of 12–14 g per day [ 20 , 34 , 54 ].…”
Section: Resultsmentioning
confidence: 99%